The Effectiveness of the Phonics Method in Improving English Reading Proficiency in Kindergarten Students - Susanti, Rr Retno Dwi (Faculty of Education Universitas Nahdlatul Ulama Yogyakarta, 2026)
This study aims to examine the effectiveness of phonics-based instruction in improving young children’s English reading skills at the kindergarten level. It is conducted within the context of English as a foreign language. Conventional alphabet-based spelling techniques often fail to meet the developmental needs of early childhood learners. Phonics, as a methodological approach to early reading instruction, emphasizes the relationship between sounds and letters and is recognized as a more structured approach. This study involved 40 students from a bilingual institution in Indonesia and employed a quantitative approach with a quasi-experimental design. Participants were divided into two groups: the experimental group received structured phonics instruction for six weeks, while the control group continued with traditional alphabet-based reading instruction. Data were collected through pre-tests and post-tests measuring letter recognition, phonemic awareness, word reading accuracy, and word decoding. The results showed that the experimental group achieved significantly higher reading scores (M = 87.6) compared to the control group (M = 70.05), with statistical significance confirmed through a t-test (p < 0.05). Qualitative data were also collected through interviews, field notes, and classroom video recordings. The findings indicate that children in the phonics group demonstrated greater engagement, enjoyment, and motivation. Students also showed positive emotional responses during phonics activities, such as singing, games, and teacher reinforcement, which supported their cognitive development and socio-emotional growth. This study concludes that phonics-based instruction is effective in improving early English reading skills, while also enhancing student engagement and emotional well-being